Codesign for InfiniBand Clusters. - Sur, Sayantan; Potluri, Sreeram; Kandalla, Krishna Chaitanya; Subramoni, Hari; Panda, Dhabaleswar K.; Tomko, Karen (Computer (00189162), 2011)
Codesigning applications and communication libraries to leverage underlying network features is imperative for achieving optimal performance on modern computing clusters.